Real-World Experience of Clascoterone Cream 1% in Acne Management: Case Series and Canadian Experience - Tay E; Loo WJ (Clinical, Cosmetic and Investigational Dermatology)
Elena Tay,1 Wei Jing Loo1– 3 1Western University, London, ON, Canada; 2DermEffects, London, ON, Canada; 3Probity Medical Research, Waterloo, ON, CanadaCorrespondence: Wei Jing Loo, DermEffects, 1560 Hyde Park Road, London, ON N6H 5L5, Canada, Tel +1 519 472 2929, Email dermeffects@gmail.comAbstract: Acne vulgaris is a globally prevalent dermatological condition associated with substantial physical and psychological burden. Although acne typically presents during adolescence, it is a chronic condition that also affects many adults. Despite the spectrum of treatments available for acne, limitations in tolerability and safety concerns can present challenges for the use of conventional medications in clinical practice. Clascoterone cream 1%, a topical androgen receptor inhibitor, was recently approved in Canada for the topical treatment of acne vulgaris. This case series included 10 patients with acne vulgaris who were treated with clascoterone cream 1% as monotherapy or part of a combination treatment program between August 2023 and May 2024. Clascoterone cream 1% was effective and well tolerated regardless of acne severity, age, gender, and ethnicity. Clascoterone led to clinical improvement when used as monotherapy, adjunctive treatment in combination with other topical or systemic agents or laser therapy, and as maintenance therapy to prevent relapse of acne. Moreover, clascoterone also helped to address other concerns in several patients, including hirsutism, hidradenitis suppurativa, retinoid-induced dermatitis, androgenetic alopecia, folliculitis, postinflammatory hyperpigmentation, and laser-induced acne flares. This early real-world clinical experience supports the effectiveness, tolerability, and versatility of clascoterone cream 1% for patients with acne across a variety of clinical and demographic characteristics.Keywords: androgen, topical, therapy, efficacy, safety, tolerability